Estudio De Factibilidad Para Invertir En Un Proyecto De Exportación De Grano De Cacao - Boyacá Colombia A La Provincia De Turín Italia. (2025)
The cocoa industry is one of the sectors with great potential in the Colombian market, in addition to being a completely natural product and traditional; since the colonial era, being a source of work and income for the peasant families of the country; and has had an increase in production in the country over the years, this project seeks to take advantage of the opportunity in the increase in cocoa production in western Boyacá, verifying if it is feasible to export cocoa beans to Italy, for this purpose projections from different studies to determine the viability of the project.